DUTY TO NOTIFY THE SELLER OF DEFECTS IN TITLE IN CONTRACTS FOR THE INTERNATIONAL SALE OF GOODS - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The seller must deliver the goods which are free from any right or claim of a third party. If the seller fails to do so he will be liable for the breach of the contract. However, the buyer loses the right to rely on the provisions regulating seller’s liability for defects in title if he does not give notice to the seller specifying the nature of the right or claim of the third party. In order to have legal effect, the notice must fulfill conditions regarding content, form and  addressee. The buyer must notify the seller in a timely manner i.e. within a reasonable time after he has become aware or, alternatively, ought to have become aware of the right or claim. Breach of the duty to notify the seller of the defects in title is followed by severe consequences for the buyer because he loses the right to rely on the defects. However, in international sales law the buyer can exercise rights arising out of defects in title even when he fails to notify the seller in two specific cases. First, the buyer retains his rights arising out of a breach of Art. 41 and 42 if the seller knew of the right or claim of the third party and the nature of it. And second, pursuant to Art. 44 of the CISG, the buyer may reduce the price in accordance with Art. 50 or claim damages, except for loss of profit, if he has reasonable excuse for his failure to give the required notice.